ANALISIS KEMAMPUAN MAHASISWA DALAM LITERASI DATA MENGGUNAKAN MODEL EMPOWERING 8 PADA TUGAS AKHIR KULIAH - Siti Fatimah; Nofrion nofrion (JURNAL BUANA, 2019)
The purpose of this research was to find ability and analyze of student geography education class of 2016 in data literacy using an empowering 8 model at the end of the lecture. This research used descriptive quantitative methods. Subject of reseach was student of Geography Education, Faculty of Social Sciences, Padang State University, class of 2016. Sampling used the Slovin formula, the sample obtained was 58 people. The technique for data collection was done trough fill questionnaires. The questionnaire created uses indicaors of standard empowering models 8. The results from this research showed ability of student geography education class of 2016 in data literacy already good with an average score of 2.89. The result showed that the presentation aspect is the highest aspect with an average score of 2.98, while the aspect of identifying data is the lowest aspect with an average score of 2.77.